Fungsi Pengawasan oleh Inspektorat dalam Meningkatkan Kepatuhan Penyelenggaraan Administrasi Pemerintahan Desa : Studi pada Desa Cijulang Kabupaten Pangandaran - Idah Hamidah Solihah; Nurdiana Mulyantini (Ebisnis Manajemen, 2024)
Government Administration plays an important role in the government's large involvement in the development process in the administrative system. For this reason, in order for development goals to really be achieved as expected, what must be considered is the existence of government officials who have competence in making village government administration. The formulation of the problem proposed in this study is How to implement the supervisory function by the Inspectorate in increasing compliance with the implementation of village government administration? What obstacles are faced in the implementation of the supervisory function by the Inspectorate in improving compliance with the implementation of village government administration? What efforts are made in the implementation of the supervisory function by the Inspectorate in increasing compliance with the implementation of village government administration? The method used is a qualitative descriptive research method. The results of the study show that the supervisory function by the inspectorate as well as the function of the supervision itself that must be carried out by the inspectorate is to strengthen the sense of responsibility of employees who are assigned tasks and authorities in the implementation of work. Educating employees to carry out their work in accordance with the established procedures. prevent negligence, weakness and irregularities so that unwanted losses do not occur, correct mistakes and misappropriations so that in the implementation of work do not experience obstacles and wastes, have been implemented in accordance with existing rules, but the results have not been able to increase compliance with the implementation of Village Government administration in Cijulang Village, Pangandaran Regency. The obstacles faced in the implementation of the supervisory function by the Inspectorate in increasing compliance with the implementation of village government administration in Cijulang Village, Pangandaran Regency, the most important are the human resources of the village government who do not want to study it and the limited auditors of the Pangandaran inspectorate, so that with a large number of villages it has an impact on the supervision process that is not in accordance with its function. Efforts made in the implementation of the supervisory function by the Inspectorate in improving compliance with the implementation of village government administration in Cijulang Village, Pangandaran Regency, are by doing the following things. An advisory services program is carried out by coming to villages to provide consulting services related to village administration management and village financial management or regarding the implementation of village government.